2007
DOI: 10.1203/pdr.0b013e3180332c2e
|View full text |Cite
|
Sign up to set email alerts
|

Brain Representation of Active and Passive Hand Movements in Children

Abstract: ABSTRACT:Several functional neuroimaging studies have been performed exploring the sensorimotor function in children with neurologic disorders. However, little is known about normal activation patterns of the sensorimotor system at a young age. We explored brain representation of active and passive hand movements in schoolage children and young adults. Nine healthy children (7-15 y) and six adults were studied. Functional magnetic resonance imaging (fMRI) data were acquired on a 1.5-T scanner in block designs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 37 publications
8
52
0
Order By: Relevance
“…Compared to the patients, activation in the HVs extended more anteriorly into the precentral gyrus and also included inferior parietal areas. Generally, these activation patterns are in line with previous evidence on the functional neuroanatomical correlates of passive movement (Ciccarelli et al, 2005;Guzzetta et al, 2007;Naito et al, 1999;Naito et al, 2002;Weiller et al, 1996) and the assumption that the afferent feedback produced by passive movement not only targets somatosensory but also motor areas (Dechaumont-Palacin et al, 2008;Fetz et al, 1980;Lemon, 1999).…”
Section: Passive Movementsupporting
confidence: 89%
“…Compared to the patients, activation in the HVs extended more anteriorly into the precentral gyrus and also included inferior parietal areas. Generally, these activation patterns are in line with previous evidence on the functional neuroanatomical correlates of passive movement (Ciccarelli et al, 2005;Guzzetta et al, 2007;Naito et al, 1999;Naito et al, 2002;Weiller et al, 1996) and the assumption that the afferent feedback produced by passive movement not only targets somatosensory but also motor areas (Dechaumont-Palacin et al, 2008;Fetz et al, 1980;Lemon, 1999).…”
Section: Passive Movementsupporting
confidence: 89%
“…Unfortunately, these studies have shown no clear consensus regarding the maturational trajectory of these networks. In one study, children who performed a simple motor task showed an increased amount of activation outside the primary motor cortex compared to adults who performed the same task (Halder et al, 2007;Muller et al, 1998) while in two others children showed a relative decrease in the amount of activation (Guzzetta et al, 2007;Mall et al, 2005). The discrepancy between the studies may result from methodological differences including the task chosen and the age-range of the subjects.…”
Section: Relationship Between Tms-evoked Parameters and Neuromotor Fumentioning
confidence: 99%
“…Much activity associated with self-initiated motor acts represents processing of polysensory (somatosensory and visual) feedback afferent information. Thus, actively and passively initiated movements overlap in terms of their functional anatomy (Weiller et al, 1996;Guzzetta et al, 2007). The present study has investigated the neural systems that distinguish between these movements.…”
Section: Introductionmentioning
confidence: 99%